KOMUNIKASI INTERPERSONAL DALAM PERSPEKTIF AL-QUR’AN (Studi Kritis Kisah Komunikasi Keluarga Ibrahim dalam Tafsȋr Ibnu Katsȋr) - Agam, Wahyu (Madani Institute : Jurnal Politik, Hukum, Ekonomi, Pendidikan dan Sosial-Budaya, 2023)
This research discusses the Al-Qur'an as the source of all knowledge turns out to give a lot of value to the science of Islamic communication, the values of the Al-Qur'an that can be instilled in interpersonal communication are; (1) qaulan karȋmâ (words full of respect), (2) qaulan balȋghâ (words that are straightforward and effective), (3) qulan ma'rȗfâ (words that are kind and full of courtesy), (4) qaulan sadȋdâ (true words and not lies), (5) qaulan layyinâ (gentle words), and (6) qaulan maysȗrâ (words that are easy to understand). The method used in this research is: qualitative research method. This research is classified as a type of library research that focuses on the theme of "interpersonal communication in the Qur'an". While the approach to this study will use a conceptual thematic interpretation approach to the story of the communication of children and parents of the Ibrahim family in the Qur'an which is integrated with communication science, or it can also be called a multidisciplinary study.